CARCASS QUALITY AND BLOOD METABOLITES OF BROILER CHICKENS FED SUPER SOSAT MILLET IN SUNFLOWER MEAL BASED DIETS - A. T. , Bello; M. , Abubakar; U. M. , Sani; N. M. , Alhassan; S. I. , Garba; M. H. , Bot; O. D. , Olaiya (Kashere Journal of Animal Science, 2025)
An experiment was conducted to evaluate the carcass quality and blood metabolites of broiler chickens fed Super SOSAT (SSM) pearl millet in sunflower meal based diets. Three hundred broiler chicks were randomly allotted to five dietary treatments in replicates of three containing 20 birds each in a completely randomized design. In the trial, Super SOSAT millet replaced maize at 0, 25, 50, 75 and 100% levels. Feed and water were served ad lib and the experiment lasted for 42 days. Results showed that all carcass indices measured were significantly (P<0.05) affected by the dietary treatments. However, only few organs showed influence of super SOSAT millet. Live weight of birds fed super SOSAT millet based diets (1.53 – 1.65 kg) were higher and similar among millet fed groups compared to the control (1.24 kg). The same trend was followed in plucked and eviscerated weights. However, carcass weight was highest (P<0.05) for birds on diet 5 (1.08kg) though did not differ from those on diets 2 (0.92 kg) and 3 (0.94 kg), followed by diet 4 (0.89 kg) and 1 (0.72 kg). In the same way, broiler chickens fed diet 5 (66.00 %) had higher dressing percent (P<0.05) than those on other diets which were the same (56.83 – 59.42 %). Organs weight as percentage of live weight showed significant influence of diets on heart weight with birds on diet 5 (0.61 %) having higher (P<0.05) weight which did not differ from that of birds on diets 1 (0.46 %) and 3 (0.52 %). Each of diets 2 and 4 had a lower value of 0.38 % which was comparable to diets 1 and 3. The weights of kidney (0.17 – 0.29 %), abdominal fat (1.86 – 2.02%) and liver (1.85 – 2.07 %) were not influenced by the replacement of maize with super SOSAT millet. Results for blood analysis showed that except for red blood cells (RBC), Mean corpuscular volume (MCV) and hydrocarbonate, no blood parameter was significantly (P>0.05) affected by the diets. The RBC count of birds on diets 5 (1.40 x 106/µl) and 4 (1.43 x 106/µl) which did not differ from those on diets 3 (1.23x 106/µl) and 1 (1.30 x 106/µl), were significantly (P<0.05) higher than that of birds fed diet 2 (1.00 x 106/µl) which was also comparable to diets 1 and 2. Conversely, packed cell volume (24.33 – 29.00 %), white blood cells (3.67 – 4.80x 103/µl), haemoglobin (5.77 – 7.33 g/dl) and cholesterol (4.50 – 6.50 mmol / l) did not differ among the diets. However, all blood parameters were within the normal reference range indicating that the birds were neither anaemic nor undernourished. It is therefore concluded that super SOSAT millet can replace up to 100% of dietary maize in sunflower meal based broiler chickens diets without significant metabolic disruptions. Based on the higher dressing percent of 66.00% for broiler chickens in diet 5 compared to the others, this diet is recommended for broiler chickens.